Bernard Shaw - McNamara, Audrey. author. aut Link
XV, 168 p.
Keywords: “This study advances an ambitious and timely thesis: namely, that Shaw’s representation of and advocacy for women’s rights (and importantly marriage rights) parallels and informs his views of the coterminous Irish nationalist project. Audrey McNamara wisely focuses her attention on plays written between 1892 and 1914, a crucial period for both movements. This interpretive goal and the structure of the argument that supports it allow McNamara to produce very fine readings of several of Shaw’s most important plays and one or two that have not received the critical attention they deserve.” — Stephen Watt, Provost Professor of English, Indiana University, USA “This timely and ground-breaking study is centrally concerned with two topics that have attracted increased interest within Shaw Studies over the past decade: Shaw’s views on marriage and his relationship to Ireland. McNamara makes insightful and original points about both of these concerns, and – even better still – she shows the relationship between them, thereby demonstrating how Shaw’s early preoccupation with marriage and the marriage question became the tool with which he interrogated the Irish question.” — David Clare, Lecturer in Drama and Theatre Studies, Mary Immaculate College, University of Limerick, Ireland Shaw emerged as a playwright in the politically charged environment of 1892, for both female suffrage and Irish independence. His plays quickly advocated for societal changes with regard to women’s roles, while expanding this advocacy into considerations of Ireland. Shaw’s engagement with marriage and union as a personal contract with nationhood have never before been considered as a methodology with which to view his work. This book demonstrates that Shaw was deeply engaged with and committed to the Irish question and to social and gender issues. Audrey McNamara lectures at University College Dublin, and is an adjunct lecturer at Trinity College Dublin, Ireland. She was guest co-editor for Shaw 36.1: Shaw and Money (2016) and co-editor for Shaw and the Making of Modern Ireland (2020).